2015
DOI: 10.1002/pssa.201532192
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric effect and critical behavior in melt-extracted Gd60Co15Al25microwires

Abstract: High-quality Gd 60 Co 15 Al 25 microwires with an average diameter of 40 mm were successfully fabricated by the meltextraction method. The as-cast microwires undergo a secondorder paramagnetic to ferromagnetic (PM-FM) transition at $100 K. Large values of the magnetic entropy change (ÀDS M $9.73 J kg À1 K À1 ) and the refrigerant capacity (RC $732 J kg 1 Introduction Magnetic refrigeration (MR) based on the magnetocaloric effect (MCE) of magnetic refrigerant materials with a first-order magnetic transition (FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
(54 reference statements)
2
4
0
Order By: Relevance
“…The fitted result is shown in Fig. 5a, which yields n = 0.77, in good agreement with those reported previously for the Gd-Al-Co microwires [16][17][18][19][20][21]. This value of n is also close to that reported previously for typical Fe-based amorphous alloys (n = 0.75) [34], but deviates from the mean-field theoretical value (n = 0.67) [33].…”
Section: S T H S T H S T Dh Tsupporting
confidence: 90%
See 2 more Smart Citations
“…The fitted result is shown in Fig. 5a, which yields n = 0.77, in good agreement with those reported previously for the Gd-Al-Co microwires [16][17][18][19][20][21]. This value of n is also close to that reported previously for typical Fe-based amorphous alloys (n = 0.75) [34], but deviates from the mean-field theoretical value (n = 0.67) [33].…”
Section: S T H S T H S T Dh Tsupporting
confidence: 90%
“…The amorphous structure of the microwires can also be predicted based on Inoue's three rules of thumb [26]: 1 ) 50 microwires is ~70 K higher than those of our previously reported Gd-Al-Co amorphous microwires (T C ~100 K) [16][17][18][19][20][21]. It has been reported that relative to GdCo binary alloys [28], the Al addition enhanced the MCE but reduced the Curie temperature in GdCoAl ternary alloys [29].…”
Section: Structural Characterizationmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, the refrigeration capacity (RC) of the wire composite was also calculated using Equation : RC=T1T2normalΔSM(T)dT where T 1 and T 2 are the onset and offset temperatures of full width at half‐maximum ( δ FWHM ) of the calculated −Δ S M ‐ T curves. The obtained RC of the composite was ≈665 J kg −1 at µ 0 Δ H = 5 T. The value was higher than that of ≈622 J kg −1 for Gd 50 Al 25 Co 25 wires, similar to that of ≈652 J kg −1 for the Gd 55 Al 25 Co 20 wire and lower than that (≈732 J kg −1 ) for the Gd 60 Al 25 Co 15 wires . The composite sample shows the average performance among its components.…”
Section: Resultsmentioning
confidence: 64%
“…The results of −Δ S M at different temperatures and applied fields are plotted in the 3D form in Figure a. The maximum magnetic entropy change (ΔSnormalMnormalmax) of the composite reaches ≈9.98 J kg −1 K −1 for a field change of 5 T, showing a similar performance compared with its components (slightly higher than that of the Gd 55 Al 25 Co 20 wire and the Gd 60 Al 25 Co 15 wire of ≈9.67 and 9.73 J kg −1 K −1 , respectively, but lower than that of the Gd 50 Al 25 Co 25 wire of ≈10.3 J kg −1 K −1 as shown in Figure b and c).…”
Section: Resultsmentioning
confidence: 96%